2020
DOI: 10.1101/2020.07.13.20152207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clinical Electroencephalography Findings and Considerations in Hospitalized Patients with Coronavirus SARS-CoV-2

Abstract: Background and Purpose Reports have suggested that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes neurologic manifestations including encephalopathy and seizures. However, there has been relatively limited electrophysiology data to contextualize these specific concerns and to understand their associated clinical factors. Our objective was to identify EEG abnormalities present in patients with SARS-CoV-2, and to determine whether they reflect new or preexisting brain pathology. Methods We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 39 publications
2
22
1
Order By: Relevance
“…The full-text screening of these studies led to the exclusion of 216 studies that did not meet the inclusion criteria. A total of 12 studies with 308 patients fulfilled the eligibility criteria for inclusion in the meta-analysis [6] , [7] , [8] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . We referred to a case report [26] of patients who were included in a case series [19] to obtain more detailed EEG findings.…”
Section: Resultsmentioning
confidence: 99%
“…The full-text screening of these studies led to the exclusion of 216 studies that did not meet the inclusion criteria. A total of 12 studies with 308 patients fulfilled the eligibility criteria for inclusion in the meta-analysis [6] , [7] , [8] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . We referred to a case report [26] of patients who were included in a case series [19] to obtain more detailed EEG findings.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent to our report, case series of COVID-19-positive patients with EEG studies (n = 13-111 each) have been published by independent groups; yet, none has incorporated COVID-19-negative patient populations exhibiting similar presentations. Among COVID-19-positive patients, the reported rates of EDs in these recently published studies varied between 0% and 38% [3][4][5][6][7][8][9][10] ; our reported 40.9% rate falls at the higher end of the spectrum. Such a spread of rates of epileptiform EEGs among small-or moderate-scale case series from different institutions exemplifies how differences in inclusion criteria, study design, patient enrollment and demographics, and clinical history may alter outcomes.…”
mentioning
confidence: 59%
“…At least 0.5% of patients have seizures as a neurological manifestation of COVID-19 infection [21]. Critical illness, acute neurologic insult, hypoxia, metabolic derangements, or organ failure can provoke seizures in patients with COVID-19 [64][65][66][67]. Seizures may also occur as a result of cortical irritation due to the interaction of SARS-CoV-2 with endothelial receptors and glial tissue receptors [68].…”
Section: Status Epilepticusmentioning
confidence: 99%
“…Use of EEG, however, is limited by the need to minimize contact to protect healthcare workers, prone-positioning, and contamination risk to equipment [66]. Thirty-eight to 40.9% of COVID-19 positive patients who had an EEG for concern of encephalopathy or seizure-like event had epileptiform discharges with frontal spikes as the predominant pattern [66,67]. The presence of epileptiform discharges was not associated with the presence of renal or hepatic failure [66].…”
Section: Status Epilepticusmentioning
confidence: 99%
See 1 more Smart Citation